2021
DOI: 10.1016/s2542-5196(20)30304-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in beverage purchases following the announcement and implementation of South Africa's Health Promotion Levy: an observational study

Abstract: Summary Background In 2016, South Africa announced an intention to levy a tax on sugar-sweetened beverages (SSBs). In 2018, the country implemented an SSB tax of approximately 10%, known as the Health Promotion Levy (HPL). We aimed to assess changes in the purchases of beverages before and after the HPL announcement and implementation. Methods We used Kantar Europanel data on monthly household purchases between January, 2014, and March, 2019, among a sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 32 publications
2
56
0
1
Order By: Relevance
“…However, there were no differences in absolute changes between groups, likely because the sample as a whole is relatively low income. For comparison, a recent pre–post study using purchase data from a nationally representative South Africa sample found greater reductions in sugar consumption (−32.7%) in LSM 4–6—nearly the identical range to our sample—compared to the higher socioeconomic group of LSM 7–10 (−20.4%) [ 42 ].…”
Section: Discussionsupporting
confidence: 39%
“…However, there were no differences in absolute changes between groups, likely because the sample as a whole is relatively low income. For comparison, a recent pre–post study using purchase data from a nationally representative South Africa sample found greater reductions in sugar consumption (−32.7%) in LSM 4–6—nearly the identical range to our sample—compared to the higher socioeconomic group of LSM 7–10 (−20.4%) [ 42 ].…”
Section: Discussionsupporting
confidence: 39%
“…The data imply that despite the beverage industry's resistance, they were able to respond to the HPL by lowering the sugar content of their beverages to lower their tax liability 23 . These studies also show that lower socioeconomic households and higher consuming or purchasers are indeed responding more in absolute terms in their reductions and thus address the health promotion goals of the HPL 22–24 . At the same time, overall sugar intakes from beverages and SSB purchases fell considerably; thus, addressing the health risk that the policy was targeting.…”
Section: Evidence Of the Effects Of The Hpl To Datementioning
confidence: 73%
“…Urban household purchases of taxable beverages post implementation fell by 29% with sugar from these purchases falling by 51%. Importantly, lower socioeconomic urban households reduced their volume and grams of sugar from SSBs by 32%% and 57%, respectively 22 A detailed collection of daily beverage intake from young (18–39 years) adults surveyed in Langa, a Western Cape township, showed a 37% reduction in volume and 31% in sugar 23 .…”
Section: Evidence Of the Effects Of The Hpl To Datementioning
confidence: 99%
See 1 more Smart Citation
“…Available evidence suggests that these sugar-density taxes in ZA and the UK have led to product reformulation. In ZA, there is a strong indication that HPL resulted in reformulation given that the sugar purchase reduction (51% lower compared to counterfactual) was larger than the volume purchased reduction (29% lower compared to counterfactual) after the tax implementation [ 20 ]. In the UK, the share of drink products subject to SDIL was 33.8 percentage points lower (compared to a counterfactual) within a year of the SDIL implementation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%